2016
DOI: 10.1095/biolreprod.116.143941
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent functions of fibroblast growth factor 9 regulate the fate of murine XY primordial germ cells†

Abstract: Male differentiation of primordial germ cells (PGCs) is initiated by the inhibition of entry into meiosis and exposure to male-inducing factor(s), which are regulated by somatic elements of the developing gonad. Fibroblast growth factor 9 (FGF9) produced by pre-Sertoli cells is essential for male gonadal differentiation and also contributes to survival and male differentiation of XY PGCs. However, it is not clear how FGF9 regulates PGC fate. Using a PGC culture system, we identified dose-dependent, fate-determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…We speculated that any such role might be in addition to and independent of the direct effects of RA on germ cell development. Such a scenario would be similar to what we know of FGF9 signaling: FGF9 reinforces the Sertoli cell differentiation pathway in males (Jameson et al, 2012a;Kim et al, 2006) but also independently promotes male germ cell development (Bowles et al, 2010;Ulu et al, 2017). The hypothesis that RA is required to feminize somatic cells during ovary development was recently addressed: the conclusion reached was that RA signaling is not required for granulosa cell specification, differentiation, or reproductive function (Minkina et al, 2017).…”
Section: Introductionmentioning
confidence: 86%
“…We speculated that any such role might be in addition to and independent of the direct effects of RA on germ cell development. Such a scenario would be similar to what we know of FGF9 signaling: FGF9 reinforces the Sertoli cell differentiation pathway in males (Jameson et al, 2012a;Kim et al, 2006) but also independently promotes male germ cell development (Bowles et al, 2010;Ulu et al, 2017). The hypothesis that RA is required to feminize somatic cells during ovary development was recently addressed: the conclusion reached was that RA signaling is not required for granulosa cell specification, differentiation, or reproductive function (Minkina et al, 2017).…”
Section: Introductionmentioning
confidence: 86%
“…Manipulation of PDGFR expression levels also showed a quantitative relationship between receptor expression levels and the vascular smooth muscle phenotype. Additional support for Marshall’s model has been provided by cell-based studies showing that changing the concentration (and thus the signaling strength) of FGF2 or FGF8, and FGF9, respectively, induces distinct responses in pre-somitic mesoderm and primordial germ cells 44 , 45 .…”
Section: Role Of Signaling Intensity and Duration In Receptor Tyrosinmentioning
confidence: 95%
“…G, Immunofluorescence assay and FCMs evaluation of SSCs production in different groups (600×) phosphorylation to inhibit MAPK/ERK signaling pathway, while up-regulation of FGFs were the opposite result. 10,12,23,24 In the process of MAPK/ERK signaling (Figure 6A), FGFR2 is a tyrosine kinase receptor that binds to FGF8, which cause tyrosine kinases to form homodimers and leads to the expression and activation of downstream genes. GRB2 is the member of the growth factor binding protein family, involved in FGFR-mediated signal transduction, RAF is the member of the MAPKK kinase family.…”
Section: Knockdown or Overexpression Fgf8 Can Inhibit Or Enhance Mapk/erk Signaling Pathway In Vitro And In Vivomentioning
confidence: 99%
“…Moreover, knockout of FGF7 can induced increased SSCs death rate. Ulu et al 10 demonstrated that FGF9 directly acts on and regulates PGCs in a dosedependent manner. It promotes differentiation into SSCs in low expression (0.2 ng/mL) while facilitates PGCs selfrenewal and inhibits differentiation when highly expressed (25 ng/mL).…”
mentioning
confidence: 99%